Price framing: monetary discount versus percentage discount format - Sutrisno, Rivan (Universitas Wiralodra, 2023)
Marketers often use price promotion as a means of stimulating sales and attracting new customers. Price promotion widely used in the market is either applying monetary discount (e.g., dollar off) or percentage discount (e.g., percentage off) format. However, no guide can be used by marketers as to which promotional format can attract customers better This systematic literature review study offers an argument that address which of the promotional format, either a monetary discount or a percentage discount, are more attractive for customers. It is concluded that the consumers favor the price promotion in monetary discount over the percentage discount format due to easier cognitive processing of the price promotion to get the actual selling price. However, the percentage discount format will attract consumers better for a low-price product since it could induce a more significant number effect.